PENGARUH PUMICE BRECCIA SEBAGAI REPLACEMENT AGREGAT HALUS PADA MORTAR INSTANT TERHADAP KUAT TARIK BELAH MORTAR - Khorunnisa, Agus Santoso (Universitas Negeri Yogyakarta, 2015)
ABSTRACTThis research aims to know the capacity of split tensile strength of the mortar andlightweight mortar composition effective for wall with using pumice breccia. Pumice breccia is anaggregate that has a good thermal insulation and easy to obtain. In addition, pumice breccia islightweight aggregate that resistant to earthquakes. However, pumice stone has not been usedoptimally for structural elements. This research was conducted with the experimental method. Inthis study, there were 27 specimens that used for testing the split tensile strength of mortar.Each type of mortar mixture comprised of 3 compositions used were normal mortar 1PC: 4PS,1PC: 6PS, 1PC: 8PS ; normal mortar pumice 1PC: 2PS: 2PM, 1PC: 3PS: 3PM, 1PC: 4PS: 4PM; pumice mortar 1PC: 4PM, 1PC: 6PM, 1PC: 8PM. The proportion of the mixture obtained fromthe calculation of the volume of the test object is used. Each composition of the mixture wasmade 3 specimens with cylinders 150 mm x 300 mm. The results showed that the split tensilestrength avarage of normal mortar, normal mortar pumice, and pumice mortar were 0,16 MPa,0,10 MPa and 0,12 MPa. The analysis results show that the optimum split tensile strengthoccurs in normal mortar pumice. Therefore, the effective proportion mix of mortar with usingpumice breccia is 1PC: 3PS: 3PM.Keywords: Mortar, Pumice, Split Tensile Strength